Soft Skill Improvement Strategy for Vocational High School Students Base on Career and 21st Century Learning Oriented (Journal of Vocational and Career Education, 2022)
The fundamental problem for vocational graduates today is the ability of soft skills which are the main basis for developing self-character to support the hard skills they have. Soft skills have a very important role in determining the character maturity of SMK graduates towards the world of work. The aims of this study were: 1) to describe the factual conditions for the soft skill development of SMK students that are integrated with the learning process and 2) to develop career-based soft skill enhancement strategies for SMK graduates oriented towards 21st century learning. The research approach used was descriptive research, followed by SWOT analysis. while the research respondents were determined through purposive random sampling method. The research results show that,SMK still has weaknesses in learning soft skills, including: 1) learning is still limited to increasing knowledge and skills (hard skills); 2) teachers, not all of them personally can become role models for students; 3) learning strategies have not yet integrated learning models based on improving students' soft skills; 4) the uneven application of Du/Di culture in the learning process; 5) lack of Du/Di support in the soft skills development of SMK students; and 6) the lack of the role of guidance and counseling in the development of soft skills. Furthermore, based on the resulting SWOT analysisthe highest score for the strength-opportunity strategy (SO: 3.53), whereimproving the soft skills of vocational students based on career-oriented learning in the 21st century, can optimize the SO strategy in all aspects, namely: 1) learning objectives; 2) basic behavior of students; 3) learning materials; 4) career-based learning strategies oriented to 21st century skills; 5) media and learning resources; and 6) learning evaluation.21st Century Learning emphasizes a balance between the development of hard skills and soft skills for SMK graduates, in order to be able to compete in the world of work and entrepreneurship, however, it is necessary to accelerate the role of various parties, especially schools in developing the character and careers of its graduates.